2009 IEEE International Electric Machines and Drives Conference 2009
DOI: 10.1109/iemdc.2009.5075359
|View full text |Cite
|
Sign up to set email alerts
|

Gearing ratios of a magnetic gear for wind turbines

Abstract: The wind turbine industry is growing at an incredible rate as numerous governments demand an increase in renewable energy generation capacity. The great multitude of turbines on windfarms throughout the world range from ones which are controlled mechanically with gears to ones which are controlled with power electronics and no gears. A drivetrain for a wind turbine which eliminates the problems of a mechanical gearbox and avoids the size and weight issues of directly-driven wind turbines is desired. A magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(45 citation statements)
references
References 5 publications
2
37
0
Order By: Relevance
“…10 illustrates the relationship between the gear ratios and key gear parameter combinations for p h = 3. It can also be seen that the lowest cogging factor is associated with fractional gear ratios, which is in a good agreement with [25], in which the authors concluded that fractional gear ratios offer the best performance for wind power applications. Comparing with the harmonic MG topology, the concentric type MG is more suited for low to medium gear ratio applications.…”
Section: Selection Of Gear Ratiossupporting
confidence: 81%
“…10 illustrates the relationship between the gear ratios and key gear parameter combinations for p h = 3. It can also be seen that the lowest cogging factor is associated with fractional gear ratios, which is in a good agreement with [25], in which the authors concluded that fractional gear ratios offer the best performance for wind power applications. Comparing with the harmonic MG topology, the concentric type MG is more suited for low to medium gear ratio applications.…”
Section: Selection Of Gear Ratiossupporting
confidence: 81%
“…We call it full magnetic indirect drive (FMID) [4]- [5]. The most attractive magnetic gears topology has been proposed by Martin [6] and was the subject of different studies proposed by Atallah [7]- [8] and others [9]- [10]. This magnetic gear can be integrated in a one or two stages of FMID like Fig.1.…”
Section: Nomenclaturementioning
confidence: 99%
“…For the various problem boundaries, conditions should be given by the equations presented in (10). From these boundary conditions, it is possible to obtain a matrix system of equations Z where the constants of integration presented in (7)- (8) are the unknowns of the problem.…”
Section: Magnetic Gearmentioning
confidence: 99%
“…In [9] and [12], it can be seen that the gear ratio and the combination of the pole-pair numbers of the two PM rings have an essential effect on the maximum torque. The effect of the pole-piece dimension on torque transmission has also been illustrated in [13], indicating that the pole-piece shape affects the magnetic flux leakage, and thereby affects the torque transmission.…”
Section: Introductionmentioning
confidence: 99%